Guidance for reconciling patent rights and disclosure of findings at scientific meetings - Singer Peter A; Mackie Jocelyn E; Lipkus Nathaniel B (BMC, 2010)
Abstract Open collaboration and sharing of information among scientists at scientific meetings can foster innovation and discovery. However, such sharing can be at odds with potential patenting and commercialization objectives. This tension may be mitigated if certain procedures are followed in the context of scientific meetings. The article first discusses what makes a scientific finding patentable and then sets out four specific patent issues for scientists to consider before attending a scientific meeting and sharing their research. Finally, it provides recommendations on how scientists can best protect their intellectual property rights while sharing information at scientific meetings.